A controllable aging sandy soil temporary shaping dry powder composite material based on seawater slurry and application thereof
Patent Information
- Application Number
- CN202611470649.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-27
AI Technical Summary
然而,该方案存在以下不足:第一,组合物为含水形态,需以液态形式运输和施用,不便于海滩现场便携使用;第二,需要额外施加CaCl2硬化液,现场操作步骤较多,普通用户尤其是儿童难以便捷操作;第三,醇类的引入虽然防止了组合物的提前凝固,但醇类对海滩环境和人体接触的适用性未予考虑;第四,技术目标为工程性长期稳定,未涉及短时塑形后自然失效的需求
1)本发明的沙土临时塑形材料为预先配制好的干粉,携带方便,现场无需进行复杂化学配制;在海滩现场可直接与海滩沙混合,并加入海水使体系成浆和交联,操作简便。相较未处理沙体,加入该材料的海滩沙具有更好的可塑形性和短时形态保持能力,从而有利于构建沙体及其他非承重造型结构。
Smart Images

Figure CN122977756A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sand shaping or temporary curing technology, and in particular to a controllable time-aging dry powder composite material for temporary shaping of sand based on seawater slurry and its application. Background Technology
[0002] Beaches are important venues for public leisure and recreation. People, especially children, enjoy playing on the beach, building sandcastles and creating sand sculptures for entertainment and relaxation, while also unleashing their creativity, making beach sand play a common scene in the tourism economy. However, because the sand grains on wet beaches rely mainly on capillary action and surface tension to form temporary connections and maintain their structure, the resulting sand structures are usually of low strength and easily collapse under the influence of gravity, water erosion, or external disturbances. It is difficult to construct stable and complex structures, thus affecting the beach sand play experience. Therefore, finding simple and economical methods to reinforce beach sand and improve its shaping and stability is of great significance and practical necessity for enhancing the recreational value of beach sand play.
[0003] In the prior art, methods for improving the structural stability of sandy soil by cross-linking sodium alginate with calcium ions have been reported. For example, US3950179 discloses an aqueous composition for stabilizing finely dispersed soil, consisting of a hydratable and swellable colloid (such as sodium alginate), water, and a C1-C4 monohydric alcohol (such as methanol). The amount of alcohol is 25%-35% of the total volume of water and alcohol to prevent the composition from solidifying before use. During use, the aqueous composition is added to the soil at a rate of approximately 5-25 gallons / foot-mile / 6-inch layer, followed by the application of a hardening agent containing a calcium source (such as CaCl2) to the soil to harden the composition. This patent also discloses that expanders such as flour, glucose, and starch can be added to the composition. However, this solution has the following shortcomings: First, the composition is in an aqueous form and needs to be transported and applied in liquid form, which is not convenient for on-site use on the beach; second, it requires the additional application of CaCl2 hardening liquid, which involves many on-site operation steps and is difficult for ordinary users, especially children, to operate conveniently; third, although the introduction of alcohols prevents the composition from solidifying prematurely, the suitability of alcohols for the beach environment and human contact has not been considered; fourth, the technical goal is long-term engineering stability, and the need for natural failure after short-term shaping has not been addressed.
[0004] For example, CN104673189A discloses a rapid film-forming dust suppressant for construction sites, composed of a sodium alginate solution with a mass concentration of 0.70%-1.0% and a calcium chloride solution with a mass concentration of 7.0%-8.0%, with a ratio of sodium alginate solution to calcium chloride solution of 1:0.75-0.90. The sodium alginate reacts with calcium chloride to rapidly form a calcium alginate film on the soil surface, covering and solidifying the surface dust. This solution has the following shortcomings: First, the product consists of two pre-prepared solutions that need to be prepared and stored separately and mixed on-site according to the specified ratio, lacking the portability of a dry powder. Second, the technical objective is long-term dust suppression, and the resulting calcium alginate film has excellent moisture absorption and retention properties, maintaining the soil's solidified moisture content above 11% for a long period, pursuing a continuous solidification effect, which contradicts the need to restore the soil to a loose state after beach recreational activities. Third, the application scenario is a construction site, without considering the marine environment and recreational conditions involving direct human contact.
[0005] For example, US4957558 discloses a temporary hardener for sand play, composed of an appropriate amount of glue and a decomposing enzyme. It is added to sand along with water to form the desired shape. The glue forms a thin film on the surface of the sand grains to maintain the shape. After a certain period, the glue is decomposed by the decomposing enzyme, destroying the sand structure and allowing the original dry sand to be recycled. While this method achieves temporary hardening and subsequent failure, its failure mechanism relies on enzymatic reactions. Enzyme activity is greatly affected by environmental factors such as temperature, pH, and seawater salinity, making it difficult to stably control the failure time in open beach environments. Furthermore, this method relies on physical bonding with glue and does not involve the formation of an ionic cross-linking network, resulting in limited short-term strength and collapse resistance of the formed structure.
[0006] In the field of sand sculpture recreational materials, US6899755B2 discloses the composition and manufacturing method of sand sculptures, including sand and a non-toxic binder soluble in cold water. The binder is selected from pregelatinized starch, chemically modified starch, and chemically modified cellulose, and the amount used is 0.1-5 parts of the dry weight of sand. This method points out that using pregelatinized starch can avoid the cumbersome operation of heating and cooking starch paste on site, making it convenient for beach use. However, the adhesive effect of this method mainly comes from the physical adhesion and water retention of starch materials. It is easily diluted and softened when exposed to continuous seawater wetting, scouring, or disturbance. It lacks a regulating structure that can provide short-term support and anti-collapse effect after shaping, and the stabilization time is limited.
[0007] Regarding the durability of sodium alginate in marine environments, a study published in Scientific Reports by Castro et al. showed that sodium alginate treatment can effectively improve the compressive strength of clean sand, with an optimal concentration of approximately 4.6%. However, under simulated wet-dry-dry cycling conditions, the unconfined compressive strength of the treated samples decreased by 26%-37% after 28 cycles, mainly attributed to the tearing of the calcium alginate film and the pressure generated by precipitated salt crystallization. SEM-EDS analysis confirmed structural damage and the accumulation of sodium chloride, calcium chloride, and calcium sulfate crystals. This study indicates that sodium alginate treatment requires supplementary measures to reduce the permeability of the treated samples, thereby improving their durability under harsh coastal conditions. Although this literature involves sodium alginate crosslinking systems in marine environments, its research objective is the long-term durability of coastal soil remediation, focusing on how to maintain the stability of the crosslinked structure under seawater erosion, which is contrary to the design approach of this application, which utilizes seawater to trigger crosslinking and achieves controllable failure through seawater action.
[0008] Furthermore, in the field of thixotropic materials, the application of lithium saponite as a thixotropic agent has been reported. Existing technologies disclose that lithium saponite expands easily upon contact with water, forming a thixotropic gel structure with high viscosity and strength, which can be used for structural reinforcement of silty soils. However, these applications are all geared towards engineering solidification or backfilling, aiming for long-term structural stability, and do not involve temporary shaping applications that synergize with sodium alginate ion crosslinking systems in seawater environments to improve the initial support capacity and anti-collapse performance of sand bodies.
[0009] In summary, the existing technology has the following shortcomings: (1) Existing sand fixation technology based on sodium alginate-calcium ion crosslinking usually uses aqueous composition or dual solution system, which requires on-site preparation, proportional mixing or additional application of hardening liquid. The operation steps are numerous and not convenient for ordinary users to use in beach environments.
[0010] (2) Existing technologies mostly use fresh water or artificially prepared solutions, and do not design formulations specifically for use under conditions where only natural seawater is taken from the beach. High concentrations of Na in seawater... + Mg 2+ Sodium alginate-Ca 2+ The effects of crosslinking systems (such as ion competition and changes in gel stability) are known in the art. The decreased durability of calcium alginate membranes in seawater environments has been reported, which makes it necessary to overcome technical obstacles to directly use seawater as a pulping and crosslinking triggering medium.
[0011] (3) Existing sand solidification technology based on sodium alginate crosslinking and thixotropic materials based on lithium saponite both pursue long-term stable structures and have not been specifically designed for the time-sensitive needs of short-term shaping, certain time retention and natural failure in beach recreation scenarios. Although US4957558 involves temporary solidification, its enzymatic failure mechanism is greatly affected by environmental factors and its stability is insufficient.
[0012] (4) Sand sculpture materials using pregelatinized starch or modified cellulose as binders mainly rely on physical adhesion and water retention. When exposed to continuous seawater wetting and scouring, they are easily diluted and softened, making it difficult to balance initial plasticity, short-term stability and later failure.
[0013] Therefore, there is an urgent need to develop a portable dry powder composite material for sand and soil that uses natural seawater as a slurry forming medium, can quickly form a temporary plastic structure under seawater triggering, and gradually fails and returns to a loose state after use. Summary of the Invention
[0014] To address the aforementioned technical problems, this invention provides a controllable time-aging sand-soil temporary plastic dry powder composite material based on seawater slurry formation and its application.
[0015] To achieve the above objectives, the present invention is implemented according to the following technical solution: The first technical solution provided by this invention is a controllable time-aging temporary plastic dry powder composite material for sand based on seawater slurry formation, which is composed of the following raw materials by mass percentage: sodium alginate 25%–34%; slurry-forming auxiliary components 12%–17%; cross-linking promoting components 9%–13%; lithium saponite 40%–53%; wherein the slurry-forming auxiliary components are one or a combination of hydroxypropyl methylcellulose and pregelatinized hydroxypropyl starch; and the cross-linking promoting components are one or a combination of calcium lactate and calcium sulfate.
[0016] Furthermore, the pulping aid component is composed of hydroxypropyl methylcellulose and pregelatinized hydroxypropyl starch in a mass ratio of 1:4 to 1:5. This pulping aid component is used to improve the pulping rate, water retention, sand grain coating, and initial plasticity of the system after the addition of seawater, and to promote a more uniform distribution of the main crosslinking component on the sand grain surface and in the interparticle spaces. The pulping aid component is not intended to form a long-term adhesive structure, but rather serves as a dispersion, coating, and pulping aid carrier for the main crosslinking component, working in conjunction with the main crosslinking component, crosslinking promoting component, and mineral regulating component to improve the short-term stability of the sand body.
[0017] Furthermore, the crosslinking promoting component is composed of calcium lactate and calcium sulfate in a mass ratio of 1:1 to 1:3, preferably, the mass ratio of calcium lactate to calcium sulfate is 1:2; wherein, calcium lactate is used to provide initially available calcium ions more quickly, and calcium sulfate is used to provide calcium ions more slowly, and the two are used together to balance the initial crosslinking speed, crosslinking uniformity and on-site shaping operation time.
[0018] Furthermore, the lithium saponite is layered magnesium lithium silicate, which appears as a loose white powder with a water content of no more than 10%, and the pH of the 2% aqueous dispersion is 10. The lithium saponite is used to improve the spatial distribution of the slurry-like binder phase and cross-linked network between sand grains, and to improve the initial support capacity, anti-collapse capacity and short-term stability of the sand body through thixotropic support.
[0019] The method for preparing the controllable time-aging temporary plasticizing dry powder composite material of sand based on seawater slurry formation of the present invention is as follows: the dry powders of the above-mentioned raw material components are uniformly mixed under drying conditions to obtain the controllable time-aging temporary plasticizing dry powder composite material of sand based on seawater slurry formation. The dry powder composite material is stored in moisture-proof packaging; if necessary, the crosslinking promoting component can be granulated, coated, or mixed in stages with the main crosslinking component, and the mineral regulating component can be premixed or mixed in stages with the slurry forming auxiliary component to improve the storage stability of the dry powder and the dispersion uniformity during field use.
[0020] The second technical solution provided by this invention is the application of the above-mentioned controllable time-aging sand temporary shaping dry powder composite material based on seawater slurry in the temporary shaping of beach sand, including the following steps: (1) Based on the quality of the dry beach sand to be shaped, the controllable time-aged sand temporary shaping dry powder composite material based on seawater slurry is directly mixed with the beach sand at a dosage of 1.8% to 4.8%. The specific mixing process is as follows: the dry powder composite material is evenly spread on the surface of the beach sand and fully mixed by manual or simple tool turning. The mixing method includes, but is not limited to, manual stirring, turning or mixing in a mold. The mixing requirement is that the dry powder is evenly distributed between the sand grains, so that a certain amount of powder is attached to the surface of the sand grains and the gaps between the grains.
[0021] (2) Natural seawater obtained on-site is directly added to the mixed sand, causing the slurry-forming auxiliary components to absorb water, swell, disperse, or dissolve, forming a slurry-like binding phase with adhesiveness, water retention, and coating properties. At the same time, the divalent or polyvalent metal ions provided by the seawater and cross-linking promoting components cause the main cross-linking components to gradually undergo cross-linking reactions. After adding water, the sand system is mixed again, further dispersing the slurry-like binding phase, main cross-linking components, cross-linking promoting components, and mineral regulating components among the sand grains, and shaping the structure in a short time to form a temporary sand body structure. Shaping methods include manual stacking, simple mold pressing, etc. Structures that can be formed include, but are not limited to, sand blocks, sandcastles, sand walls, sand pillars, and other non-load-bearing shapes for recreational purposes. The volume ratio of the added seawater to the mass of the mixed sand is 0.29–0.37 mL / g, which can be slightly adjusted according to the state of the sand body during on-site operation. For beach sand that is already wet, the amount of added seawater can be reduced accordingly based on its initial water content. When shaping sand by hand or constructing sandcastles, it is best to use sand that can be clumped together, compacted, and without significant free water.
[0022] Furthermore, the natural seawater is added in 3 to 4 batches, and the mixture is stirred after each addition to gradually hydrate and disperse the dry powder composite material until the sand reaches a plastic wet sand state. The addition methods include spraying, adding in small amounts multiple times, soaking, or direct splashing. Among these methods, spraying in batches or adding in small amounts multiple times is preferred to improve the uniformity of dry powder hydration, lithium saponite distribution, and sand particle coating.
[0023] After shaping, the slurry-like binding phase formed by the slurry-forming auxiliary components initially provides bonding, water retention, and coating, while the mineral regulating components simultaneously provide support. Subsequently, the main crosslinking components form a temporary crosslinking network under the action of divalent or polyvalent metal ions, further enhancing the connection strength between sand grains. Under the formulation and operating conditions described in the examples, the sand exhibits significant initial bonding after approximately 5–7 minutes, and forms a self-supporting temporary structure after approximately 10–12 minutes. Under continuous seawater wetting, spraying, scouring, natural drying and wetting changes, or external disturbances, the sand structure gradually softens and its strength decreases; the slurry-like binding phase is diluted or destroyed, and the temporary crosslinking network gradually loosens or breaks down, ultimately resulting in structural collapse and a return to a loose state.
[0024] The material of this invention is particularly suitable for the following scenarios: temporary sand shaping during beach children's recreational activities, temporary sandcastle and sand sculpture construction, and other non-load-bearing sand shaping during beach leisure activities. This invention leverages the interfacial characteristics of beach sand particles, utilizing a slurry-forming auxiliary component to form a slurry-like binding phase under the action of seawater, thereby improving the wetting, coating, and initial shaping capabilities of the sand particle surface. Simultaneously, it utilizes the colloidal structure regulation and thixotropic support effect of lithium saponite minerals to enhance the initial support capacity and anti-collapse ability of the shaped sand. Furthermore, it utilizes the temporary cross-linking network formed by the main cross-linking component under the action of divalent or polyvalent metal ions to improve the short-term connection strength between sand particles, enabling beach sand particles to quickly form temporary shaped structures with a certain degree of shape retention.
[0025] Compared with the prior art, the present invention has the following beneficial effects: 1) The temporary sand shaping material of the present invention is a pre-prepared dry powder, which is convenient to carry and does not require complex chemical preparation on site. It can be directly mixed with beach sand on the beach and seawater can be added to make the system slurry and cross-linked, which is simple to operate. Compared with untreated sand, beach sand with this material has better plasticity and short-term shape retention, which is beneficial for constructing sand bodies and other non-load-bearing structural shapes.
[0026] 2) This invention utilizes seawater, readily available on the beach, as a slurry-forming and triggering medium. This allows the slurry-forming auxiliary components to absorb water, swell, disperse, or dissolve, and disperse lithium saponite between sand grains. Simultaneously, the divalent or polyvalent metal ions provided by the seawater and cross-linking promoting components induce the main cross-linking components to form a temporary cross-linking network. The combined effects of these processes result in treated sand exhibiting good short-term plasticity stability and reliable on-site use.
[0027] 3) The sand structure formed by the material of this invention is not an irreversible solidified body, but a temporary structure with a certain time-limited effect. The structure can maintain its basic morphological stability for a certain period; under the continuous wetting, scouring, and spraying of seawater, the slurry-like binding phase is gradually diluted or destroyed, and the temporary cross-linking network gradually loosens or breaks down, causing the shaped body to gradually soften, collapse, and return to a loose sand state. The components used in this invention are mainly natural polymers, modified natural polymers, and inorganic mineral powders, possessing good environmental compatibility and suitable for temporary recreational and leisure activities on open beaches. Attached Figure Description
[0028] Figure 1 This is a photograph of the appearance of the cylindrical sand body used for testing in an embodiment of the present invention.
[0029] Figure 2 This is a comparison chart of the apparent compressive bearing pressure of each embodiment and the comparative example.
[0030] Figure 3This is a comparison chart of the stabilization times of each embodiment and the comparative example (excluding Comparative Example 1). Detailed Implementation
[0031] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. The specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention.
[0032] The raw materials used in this embodiment are as follows: Sodium alginate is a food-grade product. As the main crosslinking component, it undergoes a crosslinking reaction with divalent metal ions such as calcium ions to form a temporary gel network structure. Hydroxypropyl methylcellulose and pregelatinized modified starch are used as slurry-forming auxiliary components. Hydroxypropyl methylcellulose absorbs water and hydrates in a normal-temperature seawater environment, increasing the system's viscosity and water retention; pregelatinized modified starch absorbs water, swells, disperses, and forms a slurry system. Both are mainly used to improve the slurry-forming speed, sand grain coating, and initial shaping operability of the dry powder material in seawater. The crosslinking promoting component is a compound of calcium lactate and calcium sulfate, where calcium lactate pentahydrate and calcium sulfate dihydrate are used to supplement effective calcium ions and improve crosslinking uniformity and on-site shaping time. In this embodiment, the amount and mass ratio of calcium lactate and calcium sulfate are based on the actual weighed mass of the calcium lactate pentahydrate and calcium sulfate dihydrate products used. The mineral conditioning component is synthetic lithium saponite (commercially available, a layered magnesium lithium silicate, appearing as a loose white powder with a moisture content not exceeding 10%, and a pH of 10 for a 2% aqueous dispersion). This component provides colloidal structure regulation, thixotropic support, particle filling, and water retention, thereby improving the initial support capacity, collapse resistance, and short-term stability of the sand-shaped aggregate. The seawater used in the following examples is all natural seawater, used to form a slurry from the dry powder system and participate in the temporary crosslinking process of the main crosslinking component along with the crosslinking promoter. Natural beach sand is used; obvious shell fragments, stones, or debris are removed before use to reduce testing errors.
[0033] Test method: To verify the performance of the material of this invention, the following test method was used: In the observation of slurry formation and plasticity, the dry powder composite material was mixed with beach sand and then seawater was added to observe whether the system could form a plastic wet sand state. The sand body could be clumped, compacted, and shaped by hand or mold without obvious free water as the preliminary judgment criteria.
[0034] The following embodiment uses the cylindrical demolding-fixed-load method to quantitatively determine the water addition endpoint: Wet sand, after water addition and mixing, is filled into a cylindrical mold with an inner diameter of 50 mm and a height of 110 mm. After compaction and surface leveling, the mold is lifted vertically to obtain the desired result. Figure 1The cylindrical sand sample shown is kept upright. The sample has a diameter of 50 mm and a height of 110 mm. After standing for 60 seconds, a flat-bottomed loading block with a mass of 200 g and a bottom diameter of 60 mm is placed on top and held for 10 seconds. The nominal compressive stress, calculated based on the cross-sectional area of the sample, is approximately 1.0 kPa. If the sample does not collapse after unloading, and there is no visible free water on the sides, bottom, and loading contact surface, it is considered to have reached a plastic wet sand state. If the above requirements for upright holding or fixed load are not met, the amount of water added should be adjusted according to the state of the cylindrical sand sample: if the sample is loose, easily crumbles after demolding, and has no obvious free water, continue to add a small amount of seawater and mix thoroughly; if the sample shows obvious soft collapse or visible free water, it is considered to have added too much water, and no more water should be added. The above-mentioned fixed load is only used to determine the water addition endpoint and initial plasticity, and is not used as the test result of the sand body's compressive strength.
[0035] Unless otherwise stated, the cylindrical specimens used for the following observations of stabilization time, apparent compressive bearing pressure, and failure performance were all formed into cylindrical sand specimens using a cylindrical mold with an inner diameter of 50 mm and a height of 110 mm.
[0036] In the stabilization time (collapse resistance time) test, the prepared cylindrical sand sample was placed in an indoor environment and left to stand. Under conditions of no continuous spraying and no significant human disturbance, the time from the completion of molding to the appearance of obvious structural collapse, edge collapse, or continuous deformation was recorded. That is, the stabilization time is defined as the time during which the structure maintains its complete shape under conditions of no obvious deformation and no obvious collapse, that is, the time during which the structure still has basic self-supporting ability and shape retention ability.
[0037] The compressive strength was evaluated relatively using a step-by-step loading method. A cylindrical sand specimen was placed on a horizontal plane, and a known mass of loading material was gradually added to the top of the specimen. The total loading mass at which the sand exhibited significant compression, cracking, tilting, or collapse was recorded and converted to pressure per unit area (kPa) based on the specimen's cross-sectional area, denoted as the apparent compressive bearing pressure. This indicator is used for relative comparison between the embodiments and comparative examples of this invention and is not equivalent to the compressive strength measured by a standard uniaxial compression test.
[0038] In the failure performance observation, the formed cylindrical sand samples were placed under continuous seawater wetting, spraying or artificial disturbance conditions. The seawater used for wetting or spraying was the same as that used during forming, which was natural seawater. The time when obvious edge collapse, main body collapse or inability to maintain columnar shape was recorded. The sand body after failure was observed to recover to a loose or easily dispersed state.
[0039] Example 1: Take 1000 g of natural beach sand, removing obvious shell fragments, stones, and debris. Separately take 10.0 g of sodium alginate, 0.8 g of hydroxypropyl methylcellulose, 4.0 g of pregelatinized hydroxypropyl starch, 3.0 g of crosslinking promoter (including 1.0 g of calcium lactate and 2.0 g of calcium sulfate), and 12.0 g of lithium saponite.
[0040] Place the above-mentioned dry powder components into a dry container and stir thoroughly with a spoon or stirring rod until the sodium alginate, slurry-forming auxiliary components, cross-linking promoting components, and lithium saponite are basically evenly mixed to obtain a dry powder composite material. Then, evenly sprinkle the dry powder composite material on the surface of 1000 g of beach sand and mix it by hand or with a small shovel to distribute the powder as much as possible on the surface of the sand grains and between the sand grains.
[0041] After mixing, seawater was added to the sand system in four portions, with a total addition of approximately 300 mL. Each time seawater was added, the mixture was stirred and kneaded to allow the dry powder to gradually absorb water and disperse until the sand could be formed into clumps and compacted. Samples were taken and confirmed to have reached a plastic wet sand state using the aforementioned cylindrical demolding-fixed-load method. The wet sand was then packed into a cylindrical mold with an inner diameter of 50 mm and a height of 110 mm, compacted, and demolded to obtain cylindrical sand samples.
[0042] The apparent compressive bearing pressure of the obtained cylindrical sand specimen is as follows: Figure 2 As shown, it is approximately 32 kPa; its settling time is as follows. Figure 3 As shown, it takes approximately 4 hours. Under continuous seawater wetting or spraying conditions, the structure gradually softens and collapses after several hours, eventually reverting to a loose or easily dispersed sand mass state.
[0043] Example 2: Take 1000 g of natural beach sand, removing obvious shell fragments, stones, and debris. Separately take 12.0 g of sodium alginate, 1.0 g of hydroxypropyl methylcellulose, 5.0 g of pregelatinized hydroxypropyl starch, 4.5 g of crosslinking promoter (including 1.5 g of calcium lactate and 3.0 g of calcium sulfate), and 25.0 g of lithium saponite.
[0044] First, place lithium soapstone, hydroxypropyl methylcellulose, and pregelatinized hydroxypropyl starch into a dry container and stir to initially mix and disperse the fine powders. Then, add sodium alginate and cross-linking promoter, and continue stirring with a spoon or stirring rod to obtain a dry powder composite material. Next, evenly sprinkle the dry powder composite material on the surface of 1000 g of beach sand and mix it by hand or with a small shovel to distribute the powder as much as possible on the surface of the sand grains and between the sand grains.
[0045] After mixing, seawater was added to the sand system in three portions, with a total addition of approximately 380 mL. Each time seawater was added, the mixture was stirred and kneaded to allow the dry powder to gradually absorb water and disperse, preventing localized clumping. Once the sand reached a compactable, wet sand state, and samples were taken and confirmed to be in a plastic wet sand state using the aforementioned cylindrical demolding-fixed-load method, the wet sand was packed into a cylindrical mold with an inner diameter of 50 mm and a height of 110 mm, compacted, and demolded to obtain a cylindrical sand sample.
[0046] The apparent compressive bearing pressure of the obtained cylindrical sand specimen is as follows: Figure 2 As shown, it is approximately 48 kPa; its settling time is as follows. Figure 3 As shown, the time is approximately 6 hours. Under continuous seawater wetting or artificial disturbance, the structure will still gradually soften and collapse, without forming a permanently solidified body.
[0047] Example 3: Take 1000 g of natural beach sand, removing obvious shell fragments, stones, and debris. Separately take 6.0 g of sodium alginate, 0.5 g of hydroxypropyl methylcellulose, 2.5 g of pregelatinized hydroxypropyl starch, 1.8 g of crosslinking promoter (including 0.9 g of calcium lactate and 0.9 g of calcium sulfate), and 8.0 g of lithium soapstone.
[0048] Place the above-mentioned dry powder components into a dry container and stir evenly with a spoon or stirring rod to obtain a dry powder composite material. Since the total amount of dry powder composite material added in this embodiment is relatively low, after sprinkling it into the beach sand, the stirring time should be appropriately extended, and the powder should be dispersed as much as possible on the surface of the sand grains and in the gaps between the sand grains to avoid insufficient powder in some areas.
[0049] After mixing, seawater was added to the sand system in four batches, with a total addition of approximately 320 mL. Each time seawater was added, the mixture was stirred and kneaded to allow the dry powder to gradually absorb water and disperse until the sand reached a wet sand state that could be formed into clumps and compacted. Samples were taken and confirmed to be in a plastic wet sand state using the aforementioned cylindrical demolding-fixed-load method. The wet sand was then packed into a cylindrical mold with an inner diameter of 50 mm and a height of 110 mm, compacted, and demolded to obtain cylindrical sand samples.
[0050] The apparent compressive bearing pressure of the obtained cylindrical sand specimen is as follows: Figure 2 As shown, it is approximately 24 kPa; its settling time is as follows. Figure 3 As shown, it takes approximately 2.5 hours. Under continuous seawater wetting or spraying conditions, the structure softens and collapses relatively quickly, eventually reverting to a loose or easily dispersed sand mass state.
[0051] Example 4: Take 1000 g of natural beach sand, removing obvious shell fragments, stones, and debris. Separately take 10.0 g of sodium alginate, 0.8 g of hydroxypropyl methylcellulose, 3.5 g of pregelatinized hydroxypropyl starch, 4.0 g of crosslinking promoter (including 1.0 g of calcium lactate and 3.0 g of calcium sulfate), and 15.0 g of lithium saponite.
[0052] First, lithium soapstone, hydroxypropyl methylcellulose, and pregelatinized hydroxypropyl starch are placed in a dry container and stirred to initially mix the lithium soapstone with the slurry-forming auxiliary components. Then, sodium alginate and cross-linking promoters are added, and stirring is continued until the dry powder is basically uniform, resulting in a dry powder composite material. This dry powder composite material is then evenly sprinkled on the surface of 1000 g of beach sand and mixed by hand or with a small shovel.
[0053] After mixing, seawater was added to the sand system in four portions, with a total addition of approximately 340 mL. Each time seawater was added, the mixture was stirred and kneaded to allow the powder to gradually absorb water and disperse. Once the sand reached a compactable, wet sand state, and samples were taken to confirm its plasticity using the aforementioned cylindrical demolding-fixed-load method, the wet sand was packed into a cylindrical mold with an inner diameter of 50 mm and a height of 110 mm, compacted, and demolded to obtain a cylindrical sand sample.
[0054] The apparent compressive bearing pressure of the obtained cylindrical sand specimen is as follows: Figure 2 As shown, the pressure is approximately 35 kPa; its settling time is as follows. Figure 3 As shown, it takes approximately 4.5 hours. Under continuous seawater wetting or spraying conditions, the structure gradually softens and eventually reverts to a loose or easily dispersed sand mass state.
[0055] Comparative Example 1 Take 1000 g of natural beach sand, removing any obvious shell fragments, stones, and debris. This comparative example does not include any dry powder composites; it uses only beach sand and seawater mixed together.
[0056] Seawater was added to the beach sand in four separate additions, with a total volume of approximately 300 mL. After each addition, the sand was manually stirred and kneaded to ensure it was evenly moistened. Once the sand had temporarily clumped together, it was compacted into a cylindrical mold with an inner diameter of 50 mm and a height of 110 mm. After demolding, a cylindrical sand sample was obtained.
[0057] The apparent compressive bearing pressure of the obtained cylindrical sand specimen is as follows: Figure 2As shown, the pressure is approximately 6 kPa. Although sand moistened only with seawater can form a certain shape in a short time, its structure mainly relies on capillary action and surface tension after being moistened by seawater. After demolding, under continuous seawater moistening conditions, the columnar structure shows obvious edge collapse, loosening, or overall collapse within about 1 minute, making it difficult to maintain a stable shape, and quickly reverting to a loose, wet sand state. Because the sand structure in Comparative Example 1 was maintained for a very short time, it was not included. Figure 3 A comparison chart of stable times.
[0058] Comparative Example 2 Take 1000 g of natural beach sand, removing any obvious shell fragments, stones, and debris. Separately take 0.8 g of hydroxypropyl methylcellulose, 4.0 g of pregelatinized hydroxypropyl starch, 3.0 g of cross-linking promoter (including 1.0 g of calcium lactate and 2.0 g of calcium sulfate), and 12.0 g of lithium soapstone, without adding sodium alginate.
[0059] Place the above dry powder components into a dry container and mix thoroughly with a spoon or stirring rod until the hydroxypropyl methylcellulose, pregelatinized hydroxypropyl starch, cross-linking promoter, and lithium soapstone are basically evenly mixed. Then, evenly sprinkle the dry powder onto the surface of 1000g of beach sand and mix by hand or with a small shovel to distribute the powder as much as possible on the surface of the sand grains and between the sand grains.
[0060] After mixing, seawater was added to the sand system in four batches, with a total addition of approximately 340 mL. After each addition of seawater, the mixture was stirred and kneaded to allow the dry powder to gradually absorb water and disperse until the sand could be formed into clumps and compacted. The wet sand was then packed into a cylindrical mold with an inner diameter of 50 mm and a height of 110 mm and compacted. After demolding, cylindrical sand samples were obtained.
[0061] The apparent compressive bearing pressure of the obtained cylindrical sand specimen is as follows: Figure 2 As shown, it is approximately 15 kPa; its settling time is as follows. Figure 3 As shown, the time is approximately 0.6 h. Under continuous seawater wetting or spraying conditions, it easily softens and loosens, and quickly recovers to a loose, wet sand state.
[0062] Comparative Example 3 Take 1000 g of natural beach sand, removing any obvious shell fragments, stones, and debris. Separately take 10.0 g of sodium alginate, 3.0 g of cross-linking promoting component (including 1.0 g of calcium lactate and 2.0 g of calcium sulfate), and 12.0 g of lithium soapstone, without adding hydroxypropyl methylcellulose and pregelatinized hydroxypropyl starch.
[0063] Place sodium alginate, cross-linking promoter, and lithium soapstone into a dry container and stir with a spoon or stirring rod until the powders are basically evenly mixed. Then, evenly sprinkle the dry powder onto the surface of 1000g of beach sand and mix by hand or with a small shovel.
[0064] After mixing, seawater was added to the sand system in four portions, with a total addition of approximately 320 mL. After adding water, the mixture was stirred and kneaded to ensure the powder absorbed water and dispersed as much as possible. Because no slurry-forming aids were added, some areas of the powder were prone to insufficient dispersion or uneven gelation during the water addition process, requiring a slightly longer stirring time. Once the sand could be formed into clumps and compacted, the wet sand was placed into a cylindrical mold with an inner diameter of 50 mm and a height of 110 mm, compacted, and demolded to obtain a cylindrical sand sample.
[0065] The apparent compressive bearing pressure of the obtained cylindrical sand specimen is as follows: Figure 2 As shown, it is approximately 22 kPa; its settling time is as follows. Figure 3 As shown, the time is approximately 2 hours. Under continuous seawater wetting or spraying conditions, the structure gradually softens, collapses, and eventually reverts to a loose, wet sand state.
[0066] Comparative Example 4 Take 1000 g of natural beach sand, removing any obvious shell fragments, stones, and debris. Separately take 10.0 g of sodium alginate, 0.8 g of hydroxypropyl methylcellulose, 4.0 g of pregelatinized hydroxypropyl starch, and 12.0 g of lithium soapstone, without adding calcium lactate and calcium sulfate compound.
[0067] Sodium alginate, hydroxypropyl methylcellulose, pregelatinized hydroxypropyl starch, and lithium soapstone are placed in a dry container and thoroughly mixed with a spoon or stirring rod until the powders are basically evenly mixed. Then, the resulting dry powder is evenly sprinkled on the surface of 1000 g of beach sand and mixed by hand or with a small shovel to distribute the powder as much as possible on the surface of the sand grains and between the sand grains.
[0068] After mixing, seawater was added to the sand system in four batches, with a total addition of approximately 340 mL. After each addition of seawater, the mixture was stirred and kneaded to allow the dry powder to gradually absorb water and disperse. Once the sand reached a state where it could be formed into clumps and compacted, the wet sand was packed into a cylindrical mold with an inner diameter of 50 mm and a height of 110 mm and compacted. After demolding, a cylindrical sand sample was obtained.
[0069] The apparent compressive bearing pressure of the obtained cylindrical sand specimen is as follows: Figure 2 As shown, it is approximately 24 kPa; its settling time is as follows. Figure 3 As shown, it takes approximately 2.5 hours. Under continuous seawater wetting or spraying conditions, the structure gradually softens, collapses, and eventually reverts to a loose, wet sand state.
[0070] Combination Figure 2 and Figure 3 It can be seen that when the dry powder composite material described in this invention is added to beach sand, the sand gradually transforms from a loose state to a wet sand state that is graspable, compactable, and has a certain degree of cohesion and coating after seawater is added. Compared with sand that is only moistened with seawater, the sand with the material of this invention is easier to clump together, easier to demold, less likely to collapse or fall apart immediately after molding, and can maintain its basic shape for a certain period of time.
[0071] Examples 1-4 demonstrate that when sodium alginate, slurry-forming aids, a mixture of calcium lactate and calcium sulfate, and lithium saponite are present together, the sand body can form an initial bond and self-supporting structure in a relatively short time. Specifically, the slurry-forming aids facilitate the hydration, dispersion, and grain coating of the dry powder upon contact with seawater; sodium alginate forms a temporary cross-linking network under the influence of seawater and divalent metal ions provided by the cross-linking promoters; and lithium saponite helps improve the distribution of the slurry-like binder phase and the temporary cross-linking network among the sand grains, thereby enhancing the initial support capacity and anti-collapse ability of the shaped material. When these components are used in combination, they simultaneously improve the sand body's slurry-forming properties, workability, short-term stability, and long-term failure resistance.
[0072] The added seawater ratio in Examples 1 to 4 was approximately 0.29–0.36 mL / g, and all achieved the aforementioned plastic wet sand state. Therefore, it can be seen that under the initial water content of low or near-dry beach sand conditions used in this example, the added seawater range of 0.29–0.37 mL / g can meet the requirements for pulp formation and shaping.
[0073] Comparative Examples 1 to 4 show that when relying solely on seawater wetting, the sand mass mainly relies on capillary action and surface tension to maintain its shape, resulting in poor stability. While the system can form a certain viscous wet sand state when sodium alginate is lacking, it lacks the main ionic cross-linking network. The absence of slurry-forming auxiliary components reduces the hydration, dispersion, and uniformity of sand particle coating. Even without added calcium lactate and calcium sulfate, the system can still form, but the effect is slow and the stability fluctuates significantly. These comparative results indicate that the main cross-linking component, slurry-forming auxiliary component, and cross-linking promoting component all have a significant impact on the slurry formation, shaping, and short-term stability of the sand mass. In the examples, lithium saponite was used in conjunction with the above components to improve initial support and anti-collapse performance.
[0074] The stabilization time of Examples 1 to 4 under different formulations was approximately 2.5 to 6 hours, and the apparent compressive strength was approximately 24 to 48 kPa, indicating that the formulation composition and dosage affect the sand's molding and short-term stability. Based on the above results, the material of this invention can be used for temporary shaping, temporary sand sculpture construction, and other non-load-bearing sand features in beach recreation or leisure activities.
[0075] The technical solutions of the present invention are not limited to the specific embodiments described above. Any technical modifications made in accordance with the technical solutions of the present invention fall within the protection scope of the present invention.
Claims
1. A controllable time-aging temporary plastic dry powder composite material for sand based on seawater slurry formation, characterized in that, It is composed of the following raw materials by mass percentage: sodium alginate 25%–34%; pulping auxiliary components 12%–17%; cross-linking promoting components 9%–13%; lithium saponite 40%–53%; wherein the pulping auxiliary components are one or a combination of hydroxypropyl methylcellulose and pregelatinized hydroxypropyl starch; and the cross-linking promoting components are one or a combination of calcium lactate and calcium sulfate.
2. The controllable time-aging sand-soil temporary plastic dry powder composite material based on seawater slurry formation according to claim 1, characterized in that: The pulping auxiliary component consists of hydroxypropyl methylcellulose and pregelatinized hydroxypropyl starch in a mass ratio of 1:4 to 1:
5.
3. The controllable time-aging sand-soil temporary plastic dry powder composite material based on seawater slurry formation according to claim 1, characterized in that: The cross-linking promoting component is composed of calcium lactate and calcium sulfate in a mass ratio of 1:1 to 1:
3.
4. The controllable time-aging sand-soil temporary plastic dry powder composite material based on seawater slurry formation according to claim 1, characterized in that: The lithium saponite is layered magnesium lithium silicate, which appears as a loose white powder with a water content of no more than 10%, and the pH of a 2% aqueous dispersion is 10.
5. The application of a controllable time-aging sand temporary shaping dry powder composite material based on seawater slurry formation as described in any one of claims 1-4 in the temporary shaping of beach sand, characterized in that, Includes the following steps: (1) Based on the quality of the dry beach sand to be shaped, the controllable time-dependent sand temporary shaping dry powder composite material based on seawater slurry is directly mixed with the beach sand at a dosage of 1.8% to 4.8%. (2) Add natural seawater obtained on site directly to the mixed sand and soil. The volume ratio of the added seawater to the mass of the mixed sand and soil is 0.29 to 0.37 mL / g. After adding water, mix the sand and soil system again and shape the structure to form a temporary sand body structure.
6. The application according to claim 5, characterized in that: The natural seawater is added in 3 to 4 batches, and the mixture is stirred after each addition to gradually hydrate and disperse the dry powder composite material until the sand reaches a plastic wet sand state.
Citation Information
Patent Citations
Rapid film-forming dust suppressant for building construction site
CN104673189A
Stabilization composition
US3950179A
Temporary solidifier for playing with sand
US4957558A
Composition and method of forming sand sculptures
US6899755B2